CD2F-10: a new member of the CD2 subset of the immunoglobulin superfamily. - Fennelly, J; Tiwari, B; Davis, S; Evans, E (2001)
The CD2 subset of the immunoglobulin superfamily consists of a rapidly expanding family of leukocyte cell surface receptors, at least five of which (CD2, CD48, CD58, CD150, and CD244) are involved in lymphocyte activation as either receptors or ligands. Completion of the draft sequence of the human genome offers the possibility of systematically identifying the full set of proteins and interactions of this important family. Here we describe the identification and characterization of the first new member of the subset, CD2F-10, found exclusively by genome searching.